Aware and unaware- stereotypes and gender scripts in family narratives in the process of education - Magda Karkowska (Studia z Teorii Wychowania)
The aim of the article is to discuss the issues of shaping gender roles in children of early school age, taking into account the importance of stereotypes and gender scripts in this process.First of all, the basic concepts of roles, stereotypes and scripts referring to gender were presented, then I briefly reconstructed the basic assumptions of theories explaining the process of shaping a child's gender identity, in the second part of the considerations I discuss the most common patterns of female and male roles in Polish culture and present their relationships with the construction of identity, at the end I shared information on what behaviors should be avoided and how can we replace them so as not to disturb the formation of the child's ideas about functioning in gender roles. I am looking for answers to questions important from the research point of view: what role does communicative knowledge play in the process of shaping children's ideas about gender roles, and what role does conjunctive knowledge (experience) play? Is it possible to avoid stereotyping that comes from the dichotomy of gender roles in interactions with a child? How do images of gender roles become scripts? What is the significance of interference of messages from different environments (family, school, peer group) for the formation of a child's gender identity?Finally I emphasize the importance of both the narrative and dialogical character of education as a process of conscious influence on the formation of the child's ideas about gender roles (communicative knowledge), but also the broader impact of socialization processes, including intergenerational transmission (knowledge/conjuctive experience).